Minute Ventilation and Oxygen Consumption during Labor with Epidural Analgesia - Hägerdal, Magnus; Morgan, Charles W.; Sumner, Anne E.; Gutsche, Brett B. (Anesthesiology (Philadelphia), 1983)
Oxygen consumption (VO2) and minute ventilation (VE) were measured between and during uterine contractions in the first stage of labor before and after lumbar epidural analgesia (LEA) in 11 women who served as their own controls. VO2 and VE between contractions were essentially unchanged by LEA to a T10 or higher sensory level. Before LEA, both VO2 and VE were increased significantly during contractions by 63% and 74% respectively, whereas following LEA there was no significant increase in VO2 or VE during contractions. In the second stage of labor, VO2 and VE were measured in seven patients electing to have no analgesia or sedation and in 10 patients having complete pain relief produced by LEA. Measurements were obtained 5-10 min before delivery. During contractions with pushing, VO2 and VE were decreased by 25% and 31%, respectively, in patients having LEA as compared with patients having no analgesia or sedation. These results suggest that the increase in VO2 and VE are due primarily to pain associated with uterine contractions and that LEA decreased the work of breathing and the oxygen consumption of the parturient in both the first and second stages of labor.